A dual-battery storage in microgrid system using pinch analysis method - Yunus, Nik Syazreen (2023)
The energy storage system plays a crucial role in maintaining the power balance between generation and consumption in the microgrid system. Most of the microgrid normally operated with a single built in battery which is not suitable to constantly charge and discharge the energy in short intervals. By having a dual battery storage, one for charging while the other one for discharging, it can be a better solution to prolong the battery lifespan and maintain the efficiency of the battery system. This study proposed that the battery storage is split into two portions for charge and discharge by putting a rule in pinch where the battery need to first be fully charged before discharging. The methodology has been constructed using electric system cascade analysis (ESCA) to determine the efficiency and lifespan of the battery. The results showed that the microgrid system are able to obtain the optimum capacity of solar pv and the method used will be able to optimized the system by identifying the schedule of charging and discharging the batteries. The microgrid system with integration of renewable source and dual-battery energy storage system is economically feasible to meet the load demand especially during peak hours.